Anterior Approach to Thoracic and Thoraco-Lumbar Spine - Sahat Edison Sitorus (Indoscholar, 2018)
Anterior surgery approaches have been used for thoracic and upper lumbar spine. These approaches provided a very good exposure to the anterior part of vertebrae and allows for decompression of the spinal canal that help to improves neurological status in patients with neurological deficits The primary indications for the anterior approach in vertebral surgery are the conditions with the destruction of corpus vertebrae and disk diseases caused by several diseases. The aim of surgery is to decompress the neural element, reduction and stabilize the anterior part of the vertebra with and without posterior stabilization. Specifically, it could know the underlying disease and eradication of the disease. Access route is determined by the spinal and the length of the procedure, the location of the more prominent lesion, with special attention for the anatomy of the vessel, visceral, nerve, diaphragm for thoracic-lumbar approach and avoid injuring artery between T4-L4 that critical for spinal cord injury. A multidisciplinary team effort with thoracic and urologic surgeon increases the likelihood of the outcome.